Construction of a generalized Voronoi diagram with optimal placement of generator points based on the theory of optimal set partitioning - E.M. Kiseleva; L.L. Hart; O.M. Prytomanova; S.V. Zhuravel (Математичні Студії)
The problem of construction of a generalized Voronoi diagram with optimal placement of a finite number of generator points in a bounded set of n-dimensional Euclidean space is considered. A method is proposed for solving such a problem based on the formulation of the corresponding continuous problem of optimal partitioning of a set in n-dimensional Euclidean space with a partition quality criterion that provides the corresponding form of the Voronoi diagram. Further, to solve such a problem, the developed mathematical and algorithmic apparatus is used, the part of which is Shor's r-algorithm.